Two Sides of Face Learning: Improving Between-Identity Discrimination While Tolerating More Within-Person Variability in Appearance. (November 2019) - Baker, K. A.; Mondloch, C. J.
Two photos of an unfamiliar face are often perceived as belonging to different people—an error that disappears when a face is familiar. Face learning has been characterized as increased tolerance of within-person variability in appearance and is facilitated by exposure to such variability (e.g., differences in expression, lighting, and aesthetics). We hypothesized that increased tolerance of variability in appearance might lead to reduced discrimination and that misidentifications would be reduced if a face was learned in the context of a similar-looking identity. After validating our stimuli (Experiments 1a and 1b), we conducted three experiments investigating face learning. In two of these, participants learned three faces (Experiment 2: 15 images/identity and Experiment 3: 5 images/identity), two of which were similar. In a recognition task, misidentifications did not change as a function of similarity, although participants recognized more images of the target in Experiment 2 (i.e., after learning 15 images). In Experiment 4, participants learned one identity and the number of images studied varied across groups. Recognition of new images increased with the number of images studied, with no changes in false alarms; sensitivity (A′) marginally increased. The results suggest that recognition and discrimination reflect separable processes with minimal influence of between-person similarity on discrimination.